As produções dos gêneros discursivos/textuais bilhete, carta pessoal e carta aberta: um percurso escritor na eja em aulas remotas - Silva, Maria do Socorro de Araujo Sousa e (2021)
Bringing up Youth and Adult Education, we clarify that, since 1990, many researches related to language teaching have evolved in relation to the enunciative-discursive conception of language and have been promoting reading and writing practices in the classroom, for greater performance students in textual production and in linguistic analysis. It appears that many teachers work in the discursive / textual genres, including in Youth and Adult Education classes – YAE (EJA), which is a teaching modality aimed at those who were unable to attend the regular course, or who, for various circumstances, had to leaving school and that after a few years returned to the classroom to have access to education. The present study aimed to produce the Ticket, the Personal Letter and the Open Letter, which are current discursive / textual genres, starting from the simplest, to an average, until reaching a more formal writing, and are instruments that have a social function. This study turned at a class of 8th grade YAE (EJA), from the second segment, in Portuguese language classes, at a school in the municipality of Rio Tinto / PB. For that, we used the didactic sequence proposal recommended by Dolz; Noverraz; Schneuwly (2011) and we used as strategies, as methodological procedures, the observation and the didactic sequence, operational instruments that served as practical mediation for the realization of the qualitative study that we carried out, which was guided around the action research. Our object of study with the target audience was the production of discursive / textual genres Ticket, Personal Letter and Open Letter, with the purpose of instigating students to writing. Therefore, we are based on the theoretical assumptions of Bakhtin (2011) and Marcuschi (2007 and 2016). With regard to teaching using the media apparatus, we focus on the concepts of Moran (2012) and Soares (2002), among others. We carried out our intervention in the course of 10 (ten) remote classes, in view of the COVID-19 pandemic we are going through, which took away the possibility of conducting face-to-face classes. Therefore, we work with each genre, and from the students' initial writings, we observe their difficulties in relation to the spelling, accentuation, verbal agreement and argumentation. After that, we elaborated the classes for the application of the didactic sequences, which culminated in the final writings, which pointed to the learning of the writing of the genres worked and the knowledge of their functions in society, from the intervention sequences offered. The results were satisfactory, since they increased the written capacity of the students participating in the study, in relation to the type of teaching taught.